2016
DOI: 10.1007/s00221-016-4747-9
|View full text |Cite
|
Sign up to set email alerts
|

Drawing sounds: representing tones and chords spatially

Abstract: Research on the crossmodal correspondences has revealed that seemingly unrelated perceptual information can be matched across the senses in a manner that is consistent across individuals. An interesting extension of this line of research is to study how sensory information biases action. In the present study, we investigated whether different sounds (i.e. tones and piano chords) would bias participants' hand movements in a free movement task. Right-handed participants were instructed to move a computer mouse i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 80 publications
0
15
0
1
Order By: Relevance
“…In humans, another example of grounding can be found in cross-linguistic research, which shows that the understanding of some concepts (e.g. emotion) is closely related to the perception of physical space (Montoro, Contreras, Elosúa, & Marmolejo-Ramos, 2015;Salgado-Montejo et al, 2016). Therefore, it is reasonable to hypothesise that, while some elements of human cognition are more or less universal, they are still grounded in a material reality.…”
Section: Grounded Experiencementioning
confidence: 99%
See 2 more Smart Citations
“…In humans, another example of grounding can be found in cross-linguistic research, which shows that the understanding of some concepts (e.g. emotion) is closely related to the perception of physical space (Montoro, Contreras, Elosúa, & Marmolejo-Ramos, 2015;Salgado-Montejo et al, 2016). Therefore, it is reasonable to hypothesise that, while some elements of human cognition are more or less universal, they are still grounded in a material reality.…”
Section: Grounded Experiencementioning
confidence: 99%
“…Some studies have demonstrated clear links between concrete and abstract domains by asking participants to perform various body movements, or to place valenced objects in space (positive items go "up", negative items go "down"). This has been shown to have an effect on memory, emotional state, and semantic space processes (Casasanto, 2009;Salgado-Montejo et al, 2016;Vigliocco, Vinson, Lewis, & Garrett, 2004). Lakoff and Johnson (1980) proposed that something as abstract as metaphors can be grounded in bodily experience.…”
Section: Abstract Conceptsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also fundamental is the correspondence of sensory features, e.g. size and timbre, size and pitch, and the particularly well studied correspondence between spatial elevation and pitch (Melara & O'Brien, 1987;Ben-Artzi & Marks, 1995;Patching & Quinlan, 2002;Maeda et al, 2004;Widmann et al, 2004;Evans and Treisman, 2010;Spence, 2011;Salgado-Montejo et al, 2016). Interestingly, this ability may still be true when one of these features is nonconscious.…”
Section: Introductionmentioning
confidence: 99%
“…De fato, esta é uma das correspondências mais estudadas (Melara & O'Brien, 1987;Ben-Artzi & Marks, 1995;Patching & Quinlan, 2002;Maeda et al, 2004;Widmann et al, 2004, Salgado-Montejo et al, 2016. Contudo, apesar destas demonstrações, inclusive em bebês, Parise (2016) levanta dúvidas sobre este mapeamento natural, que pode ter relações bayesianas de uma vida sendo exposta ao mesmo tipo de relação (Parise, 2016).…”
Section: Integração Multissensorialunclassified